2010
DOI: 10.1016/s1658-3655(12)60017-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of microbial pathogens in blood cultures: an etiological and histopathological study

Abstract: Performance of BACTEC 9120 blood culture system was compared with the conventional (manual) broth method in detecting blood cultures of 500 patients suffering from various diseases. The BACTEC system proved to be superior in both yield and speed of detection. Four species of yeasts belonging to 2 genera and 13 species of bacteria belonging to 12 genera were recovered from the patient's blood cultures. The study confirmed the serious role of yeasts present in patient blood, and highlighted the serious pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(23 reference statements)
1
4
1
Order By: Relevance
“…Furthermore, our study increased BC sampling from 24 to 63 BC per month. These findings are in accordance with other studies in resource-limited settings (12,20). Additionally, the proportion of false-positive BC and therefore the workload could be reduced with automated BC significantly.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, our study increased BC sampling from 24 to 63 BC per month. These findings are in accordance with other studies in resource-limited settings (12,20). Additionally, the proportion of false-positive BC and therefore the workload could be reduced with automated BC significantly.…”
Section: Discussionsupporting
confidence: 92%
“…Contamination of BC was high in automated and manual BC (48 and 43%, respectively), although clinical training on good practice BC sampling supported our study. The proportion of contaminated BC was higher in our study than in comparable studies in resource-limited settings and above the targeted 3% (20,(22)(23)(24). As most contaminants belonged to the typical flora of the skin, we assume that contamination occurred during sampling due to insufficient disinfection.…”
Section: Discussioncontrasting
confidence: 58%
“…This is obviously longer than what is currently seen with automated systems, where 82–91.6% of growth is detected within 24 h (249251). Some recent studies from LMICs, directly comparing manual with automated systems, also found higher sensitivity, specificity and especially much lower time-to-detection with the automated system (24–26).…”
Section: Challengesmentioning
confidence: 99%
“…During incubation, the bottles are continuously agitated in the automated equipment. The current automated systems show better performance than manual systems in terms of yield and especially speed of growth, as recent studies from LMICs such as Egypt, Pakistan, and India have shown (24–26). However, these automated systems are costly, require regular maintenance and are not adapted to tropical, dusty environments, impeding the sustainable implementation of this technique in many LMICs outside of study sites, large reference laboratories or private laboratories in the capital cities (1, 27).…”
Section: Introductionmentioning
confidence: 96%
“…Carbon dioxide generated by the growing microorganism is measured in either a fluorescent or colorimetric way [17]. Although adopting such technologies showed substantially increased sensitivity [18][19][20], the high costs associated with the device and blood culture bottles, regular instrument maintenance, and the infrastructural issues prevent their wide usage in low-income and developing countries [17]. As a result, manual culture systems are more popular in these regions.…”
Section: Blood Culture Bottles: Automated or Manual?mentioning
confidence: 99%